Cognitive Biases Influence Clinical Practice of Selective Removal of Carious Tissue by Dentists and Students: An Exploratory Study - Moreira, Jefferson Chaves; Caneppele, Taciana Marco Ferraz [UNESP]; Bresciani, Eduardo [UNESP] (FapUNIFESP (SciELO), 2024)
Objective: To determine whether there is a lack of diffusion in the knowledge of selective removal of carious tissue (SRCT) and to examine whether cognitive biases influence professionals in their decision to implement SRCT. Additionally, this study seeks to identify whether the lack of knowledge diffusion and cognitive biases act as barriers to the adoption of SRCT in practice. Material and Methods: A series of questions was administered to dental professionals aiming to assess their knowledge of SRCT, their opinions on its use, and whether they incorporated this technique. Some questions were designed to identify potential factors influencing their decision-making process. The data was presented in terms of frequency percentages and analyzed using association tests (p>0.05). Results: Out of 568 respondents, fifty-four individuals (9.5%) were not in favor of SRCT, while eighty-nine did not implement it in their practice. Professionals who were less inclined to use SRCT included those who had not studied it, endodontists, specialists unrelated to dentistry/pediatric/dental clinic, and dentists who had completed their degrees more than four years ago. Cognitive biases, such as outcome bias, overconfidence bias, and bias against new beneficial therapies, were found to be influenced by SRCT knowledge, specialized fields, postgraduate education, and the duration of professional training. Regarding the removal of carious tissue at pulp walls in very deep cavities, 158 respondents answered correctly, while 410 respondents provided incorrect responses. Conclusion: A deficiency in the dissemination of SRCT knowledge was identified. Cognitive biases exerted a significant influence on decision-making concerning the removal of carious tissue. These two findings contribute to the limitation in translating SRCT into clinical practice.
Keywords: Dental Caries; Education, Professional; Evidence-Based Dentistry; Heuristics